2020
DOI: 10.1111/bcp.14556
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic evaluation of cefuroxime in perioperative antibiotic prophylaxis during and after cardiopulmonary bypass

Abstract: CR, CL, DH, BE, GW and GH conceived the study. CL, MM and HW recruited patients and collected clinical specimens. MF performed HPLC analyses. All authors contributed to data analysis and writing of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Studies found that despite cefuroxime target-attainment drug levels being reached after their perioperative administration, such levels could not be maintained in the immediate postoperative period, which could explain why it was insufficient as a monotherapy strategy [28]. In comparison, ceftriaxone levels seem to be higher but not enough to completely protect against Pseudomonas in monotherapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that despite cefuroxime target-attainment drug levels being reached after their perioperative administration, such levels could not be maintained in the immediate postoperative period, which could explain why it was insufficient as a monotherapy strategy [28]. In comparison, ceftriaxone levels seem to be higher but not enough to completely protect against Pseudomonas in monotherapy [29].…”
Section: Discussionmentioning
confidence: 99%
“…The recommended proposal is similar to the American Clinical Practice Guidelines for Antimicrobial Prophylaxis in Surgery [28] . Christer Rimmler [29] reported that dosing recommendations for CXM as perioperative AP in cardiac surgery are su cient to reach plasma unbound concentration to cover S. aureus during the operation. However, J Lanoiselée et al [30] stated common dosing regimens of 1.5 g CXM recommended by US and European guidelines did not sustain therapeutic concentrations throughout cardiac surgery and proposed an optimized dosing regimen according to the population analysis of CXM pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%